2016
DOI: 10.1007/s11239-016-1378-8
|View full text |Cite
|
Sign up to set email alerts
|

Prescriber knowledge and attitudes regarding non-administration of prescribed pharmacologic venous thromboembolism prophylaxis

Abstract: Pharmacologic venous thromboembolism (VTE) prophylaxis is important patient safety practice in hospitalized patients. However, a substantial number of ordered doses are not administered. Patient and nursing attitudes and behaviors can influence whether a patient receives a dose. The objective of this single center study was to evaluate prescriber knowledge and attitudes regarding missed doses of pharmacologic VTE prophylaxis. An anonymous, 9-question survey was administered to internal medicine and general sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…In a survey of 122 resident physicians, we found significant differences in clinical practice between medicine and surgery residents. Medicine residents were more likely to believe that VTE prophylaxis was overprescribed, and that it was appropriate for nurses to make judgement calls about whether patients needed the prophylaxis that was prescribed . In a mixed methods study that included a written survey and qualitative observations of nursing practice, we found that some nurses presented pharmacologic VTE prophylaxis injections as optional to patients.…”
Section: Improving Vte Prophylaxis Administrationmentioning
confidence: 93%
See 2 more Smart Citations
“…In a survey of 122 resident physicians, we found significant differences in clinical practice between medicine and surgery residents. Medicine residents were more likely to believe that VTE prophylaxis was overprescribed, and that it was appropriate for nurses to make judgement calls about whether patients needed the prophylaxis that was prescribed . In a mixed methods study that included a written survey and qualitative observations of nursing practice, we found that some nurses presented pharmacologic VTE prophylaxis injections as optional to patients.…”
Section: Improving Vte Prophylaxis Administrationmentioning
confidence: 93%
“…Medicine residents were more likely to believe that VTE prophylaxis was overprescribed, and that it was appropriate for nurses to make judgement calls about whether patients needed the prophylaxis that was prescribed. 21 In a mixed methods study that included a written survey and qualitative observations of nursing practice, we found that some nurses presented pharmacologic VTE prophylaxis injections as optional to patients. Furthermore, nurses on units where nonadministration was higher were more likely to believe that VTE prophylaxis was prescribed for patients unnecessarily, and that they could use their clinical judgement to determine when it was appropriate to omit doses of pharmacologic prophylaxis.…”
Section: Improving Vte Prophylaxis Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Inconsistencies among and between providers may lead to variable practices, especially in management of conditions that are perceived as "low risk" such as holding a single dose of a medication. [29][30][31][32] In addition, the multidisciplinary nature of surgical patient care, wherein surgical, anesthesia, acute pain, and other consulting providers are involved can create confusion regarding which service takes charge of which element in care. In reviewing the nursing notes, most of the doses held for epidural had a specific comment associated with the epidural being removed.…”
Section: Discussionmentioning
confidence: 99%
“…traveling nurse, float nurse) were excluded from this study. Because of known differences between medical and surgical floors in VTE prophylaxis administration practice and culture,[ 14 , 16 , 19 21 ] floors were stratified by department (i.e. medicine and surgery) for randomization.…”
Section: Methodsmentioning
confidence: 99%